Pengaruh Jumlah Wisatawan, Jasa Pendidik, Jumlah Penduduk Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Di Daerah Istimewa Yogyakarta Studi Kasus 5 Kabupaten 2010-2015) - Azizah, Annisa Wakhidatul; , Maulidyah IH., Ir,MS (2017)
In the Special Region of Yogyakarta is an area that has a relatively Gross Domestic Regional Income rising. Inter-regional cooperation is expected to create an equitable development of the economy in the Special Region of Yogyakarta can be more advanced and evenly. This study aims to determine the influence of the number of tourists to the GRDP in the Special Region of Yogyakarta, to know the influence of Educator Services to PDRB, to know the effect of the Population and to know the effect of Government Expenditure on GRDP. The method in this research using panel data regression analysis by using model of FEM (Fixed Effect Model).The result of this research shows that government expenditure variable has positive and significant influence to GRDP in Yogyakarta Special Region, the variable of Number of Tourist, Educator Service and Number of ulation does not positively influence to PDRB in Special Region of Yogyakarta.